Circulating Cytokines and Lower Body Muscle Performance in Older Adults at Hospital Admission - Garcia-Hermoso, A (Serdi-Editions, 2020)
Background: Aging-related traits, including gradual loss of skeletal muscle mass and chronic inflammation, are linked to altered body composition and impaired physical functionality, which are important contributing factors to the disabling process. We sought to explore the potential relationship between lower-body muscle strength decline and inflammatory mediators in older adults. Methods: We performed a cross-sectional analysis in 38 older adults admitted to an acute care of the elderly unit (57.9% women, mean age=87.9±4.9 years; mean body mass index [BMI]=26.5±4.7 kg/m2). Clinical and functional outcomes including weight, height, BMI, dependence, physical and cognitive performance, and muscle strength measured by one-repetition maximum (1RM) for leg-extension, leg-press, chest-press and handgrip strength, were assessed. Blood serum content of 59 cytokines, chemokines and growth factors was assessed by protein arrays. Multivariate linear regression analyses were used to examine the relationship between cytokine concentrations and muscle strength parameters. Results: After controlling for confounding factors (age, sex, BMI, cumulative illness rating score and physical performance score), 1RM leg-press had a significant negative relationship with GRO (CXCL2) (β= −18.13, p=0.049), MIG (CXCL9) (β= −13.94, p=0.004), IGF-1 (β= −19.63, p=0.003), CK-BETA 8 (CCL23) (β= −28.31, p=0.018) and GCP-2 (CXCL6) (β= −25.78, p=0.004). Likewise, 1RM leg-extension had a significant negative relationship with IGFBP-1 (β= −11.49, p=0.023). Conclusions: Thus, several serum cytokines/chemokines and growth factors are negatively associated with lower muscle strength in older patients. Further investigation is required to elucidate the mechanism of elevated inflammatory mediators leading to lower muscle strength. © 2020, Serdi and Springer-Verlag International SAS, part of Springer Nature.